Equilibrium, kinetics, and thermodynamics of moisture adsorption on plastic encapsulated microcircuits - Gustilo, Paul Angelo D. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The mold compound of plastic encapsulated microcircuits (PEMs) is susceptible to moisture sorption which can lead to device failure especially on application specific high stress environment. Some of the moisture-related failure mechanisms for integrated circuit (IC) PEMs include corrosion, hygroscopic swelling, delamination, bond wire breakages, package cracks, and leakage failures. In high voltage and high humidity conditions, leakage failure may develop as a result of a thin layer of moisture saturated skin on the surface of the plastic package. Unlike the other aforementioned failures, leakage failures occur even when the package is not fully saturated with moisture. This study aims to characterize the equilibrium, kinetics, and thermodynamics of moisture adsorption on plastic encapsulated microcircuits using classical adsoption models. Using digital isolator IC as test sample, industry standard moisture exposure conditions are used to create a pseudo-adsorptiuon isotherm for the moisture-mold compound adsorption system of a 16 lead SOIC package. Goodness-of-fit between experimental data and applicable model is assessed using coefficient of determination (r^2) and total mean error (ε%). The moisture-mold compound pseudo isotherm best fits the Freundlich model, which is indicative of adsorption on heterogeneous surface sites, with r^2=0.9512 and ε=13.64%. Such may be expected, given that the mold compound is composed of silica fillers in an epoxy matrix. Moisture adsorption best fits the pseudo second order Elovich kinetic model, which is consistent for gas-solid adsoption, with r^2=0.9816 and ε=4.46%. First approximation of the thermodynamic feasibility of the adsorption process is also estimated with Gibb's free energy calculated to a negative value indicating spontaneity and is within the physisorption range; the enthalpy of adsorption is calculated to a positive value indicating endothermic adsoption; while the entropy of adsorption is calculated to a slightly positive value suggesting a slight increase in randomness of moisture molecules once fixated to adsoption sites on the surface of the plastic mold compound.
Thesis (M.S. Metallurgical Engineering)--University of the Philippines, Diliman.
Keywords: Electronic packaging -- Materials -- Absorption and adsorption; Electronic packaging -- Moisture; Integrated circuits; Plastic encapsulated microcircuit (PEM).